Efficacy of a nutrition education intervention designed to improve overall diet quality of female adults - Khan, Hira (Progress in Nutrition, 2018)
Objective: Determine the effectiveness of a nutrition education (NE) intervention in improving nutritional knowledge and diet quality. Design: Quasi experimental with a control group. Setting/Participants/Intervention: Fifty six female undergraduate students aged 18-24 years. The experimental group (n=28) received 44 sessions of NE lectures while the control group (n=28) received no intervention. Main Outcome Measures: Questionnaire with nutrition knowledge questions, semi-quantitative FFQ distributed at pre-test, posttest (3M) and posttest 2 (6M). USDA food composition tables were utilized to calculate a Diet Quality Index-International (DQI-I) score. Analyses: Analysis through SPPS with significance at p <.05. Results: Mean knowledge scores in only the experimental group increased significantly between the 3 stages (p=.000) from 9.03 vs. 11.85 vs. 12.85. In the control group, calcium and vitamin C intake decreased and in the experimental group, there was a significant increase in fiber (21.40 vs. 23.56 vs. 27.30g) and calcium intake (674.96 vs. 690.60 vs. 852.85 mg). DQI-I score of only the experimental group increased (53.25 to 56.36 to 65.93) and post hoc test revealed 6 months of NE were required to significantly increase diet quality (p=.000) specifically variety (p=.008) and adequacy (p=.001) subcomponents. Conclusions: Nutrition courses play a valuable role in improving diet quality